Social and historic conditionality of the concepts of law and their representation in fiction - Нестеренко, Ксенія Вікторівна (Problems of legality, 2016)
The article proves the necessity of integrated approach to the research into legal concepts representation in fiction, using knowledge, methods and instruments of literary, legal and cultural studies. Such approach helps to reveal common and distinct features of legal concepts content in the pieces of literature, and mark out timeless or temporary content in them.